DETECTING CHANGES IN MANGROVE FORESTS FROM MULTI-TEMPORAL SENTINEL-2 DATA IN TIEN YEN DISTRICT QUANG NINH PROVINCE - Quyet, Nguyen; Hai Hoa, Nguyen; Dai, Vo; Duy Quang, Pham (Journal of Forestry Science and Technology, 2021)
Mangrove forests are intertidal wetlands and found along tropical, subtropical, and warm-temperate coastlines. They also offer valuable ecosystem services. However, mangrove forests are especially vulnerable as typhoons frequently hit during the monsoon season and under driving human pressures. The spatio-temporal change information of mangrove forest cover distribution in Tien Yen district is incomplete. Thus, this study was undertaken to detect spatial-temporal distribution of mangrove forests in Tien Yen district and then identify the drivers of mangrove cover change. Multi-temporal Sentinel-2 data were used to detect changes in the extent of coastal mangrove forests using the NDVI thresholds combined with the visual interpretation. Three land use and land covers were categorised, namely mangrove forests, non-mangrove forests, and water bodies. Mangrove forests in Tien Yen district were estimated to be 3133.8 ha in 2015 and decreased by 277.8 ha in 2020. Aquaculture, shrimp farm and agriculture expansion, and other land uses were the main drivers for mangrove deforestation during the period of 2015 - 2020. This study used the NDVI thresholds for coastal land covers (NDVI value > 0.2 for mangrove forests). The overall accuracies assessments of land covers in 2020 (reached 91.3%, Kappa coefficient of 0.83) and land covers in 2016 (assessed at 88.3%, Kappa coefficient of 0.78) have confirmed the effectiveness of using remotely sensed Sentinel-2A/B for monitoring the spatio-temporal changes of mangrove forests in Tien Yen district.